2021
DOI: 10.1097/j.pain.0000000000002390
|View full text |Cite
|
Sign up to set email alerts
|

Can placebo and nocebo effects generalize within pain modalities and across somatosensory sensations?

Abstract: Supplemental Digital Content is Available in the Text.Placebo and nocebo effects induced by verbal suggestion and conditioning can generalize across pain modalities, but generalization to itch does not necessarily take place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Neural mechanisms that support these psychological processes may be similar across clinical outcomes, although downstream mediators of placebo effects are likely to differ across conditions. Although few studies have compared placebo effects across modalities [42,[64][65][66][67], a larger literature focuses on whether the brain mechanisms that process pain (and show reductions with placebo) are unique to pain. In the following section I review brain mechanisms of placebo analgesia and evaluate evidence regarding pain specificity.…”
Section: Brain Mechanisms Of Placebo Analgesia and Specificity To Painmentioning
confidence: 99%
“…Neural mechanisms that support these psychological processes may be similar across clinical outcomes, although downstream mediators of placebo effects are likely to differ across conditions. Although few studies have compared placebo effects across modalities [42,[64][65][66][67], a larger literature focuses on whether the brain mechanisms that process pain (and show reductions with placebo) are unique to pain. In the following section I review brain mechanisms of placebo analgesia and evaluate evidence regarding pain specificity.…”
Section: Brain Mechanisms Of Placebo Analgesia and Specificity To Painmentioning
confidence: 99%
“…Second, as this nocebo itch study consisted of only a single session, further study could investigate how long the induction and (response) generalization of nocebo effects persist. Third, although the findings suggested some links between the induction of nocebo effects and their generalization, it remains unclear whether nocebo responders are more prone to generalization effects than non‐responders 16 . Exploring the role of responders' characteristics in generalization of nocebo effects will help in individually predicting the prevalence of nocebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…This is called response generalization, where a generalization response is alike the previous response (eg nocebo hyperknesis) to a stimulus, upon exposure to a cue (eg nocebo solution) 17 . For instance, indirect evidence showed that nocebo effects generalize from electrically evoked itch to histamine‐evoked itch 15,16 . Theoretically, generalization effects are stronger when the outcomes are more similar 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain may be nociceptive, neuropathic or mixed ( Angst et al, 2020 ). There is evidence that the cytokine profile in COVID-19 contributes to the promotion of pain and also improves pain states ( McFarland et al, 2021 ; Weng et al, 2021 ), and that SARS-CoV-2 infection may worsen neural damage or neural pain in leprosy patients.…”
Section: Introductionmentioning
confidence: 99%